An application of general branching processes to a cell cycle model with two uncoupled sub-cycles and unequal cell division - Alexandersson, Marina (Zielona Góra: Uniwersytet Zielonogórski)
A cell population model is constructed and analysed in the framework of general branching process theory. The model uses the idea that the DNA division cycle and the cell growth cycle are loosely coupled. The cell division is assumed to be unequal and the structure variables of the model are size and growth, where the growth is regulated by supramitotic growth control.
Keywords: branching process; cell cycle model; unequal cell division; stable type distribution; [alpha]-curve; [beta]-curve; mother-daughter correlation